2021
DOI: 10.5433/1679-0359.2021v42n3supl1p1397
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging predicts the emergence of rice seedlings in the field

Abstract: Selecting the most appropriate vigor test for rice to predict seedling emergence remains a challenge. This is mainly attributed to the diversity of available tests that evaluate vigor; however, there is a critical need for tests that can show a high correlation with field emergence. Thus, this study aimed to determine which vigor tests are the most efficient in predicting the emergence of rice seedlings, to facilitate correct selection for quality control analyses and pre-sowing for rice seed commercialization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, in the 2020/2021 growing season, the high-vigor lots presented an average vigor by AA percentage of 90%, which was significantly higher (p < 0.05) than the vigor by AA obtained for the low-vigor lots (64%) (Table 1). According to the literature, vigor by AA presents a high correlation with seedling emergence in the field and is, therefore, considered one of the most efficient parameters for predicting seedling emergence (Garcia;Coelho, 2021). This is because vigor by AA simulates, in the laboratory, the adverse conditions that the seeds would encounter in the field at the time of emergence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the 2020/2021 growing season, the high-vigor lots presented an average vigor by AA percentage of 90%, which was significantly higher (p < 0.05) than the vigor by AA obtained for the low-vigor lots (64%) (Table 1). According to the literature, vigor by AA presents a high correlation with seedling emergence in the field and is, therefore, considered one of the most efficient parameters for predicting seedling emergence (Garcia;Coelho, 2021). This is because vigor by AA simulates, in the laboratory, the adverse conditions that the seeds would encounter in the field at the time of emergence.…”
Section: Resultsmentioning
confidence: 99%
“…This difference in the performance of seedlings between the lots with contrasting vigor was also reported by Abati et al (2018) and Marinho et al (2021), who observed, in separate studies conducted on wheat, that the use of vigorous seeds resulted in a greater number of emerged seedlings compared to the use of non-vigorous seeds. This is because high-vigor seeds have a higher rate of seedling development in the field, even under unfavorable conditions, which results in an adequate initial establishment (Carvalho;Nakagawa, 2012;Garcia;Coelho, 2021).…”
Section: Resultsmentioning
confidence: 99%